Circumstances of death from asthma. Issue 6434 (23rd June 1984) - Johnson, A J; Nunn, A J; Somner, A R; Stableforth, D E; Stewart, C J
Abstract : Mortality from asthma in England and Wales has remained unchanged for at least 20 years, even in the age group 15-44. Yet in those 20 years "modern" drugs have been introduced for the treatment of asthma, such as beta 2 agonist bronchodilators and corticosteroids. Why do patients still die? Detailed review of the circumstances of 90 deaths from asthma showed that a few were inevitable but that in the remainder four main sets of circumstances in the fatal attack contributed to the death. These were, firstly, the patient's failure to recognise the severity of the asthma; secondly, very rapid progress in the severity of the attack; thirdly, misjudgment in the management of the attack; and, fourthly, delay from many causes. Patients admitted to hospital with severe acute asthma usually survive. Those at risk of a life threatening attack should be identified and taught to monitor the severity and progress of their asthma objectively. Their direct admission to hospital should be facilitated.